2019
DOI: 10.3390/app9235091
|View full text |Cite
|
Sign up to set email alerts
|

MSWI Bottom Ash Application to Resist Sulfate Attack on Concrete

Abstract: This research provides a strategy for partially replacing cement with municipal solid waste incineration (MSWI) bottom ash (BA) to improve the performance of concrete against sulphate attack. Mortar strength tests were performed firstly to evaluate the hydration activity of the ground BA. Concrete specimens were cured in standard conditions and immersed in a solution that contained 10% sodium sulfate. Then, the compressive strength of these specimens was measured to investigate the mechanical properties and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The aggregate included natural river sand with a fineness modulus of 2.87 and basalt gravel with a continuous gradation of 5-20 mm in particle size. Replacing cement with 20% fly ash had been reported to significantly improve the resistance of concrete to sulfate attack [24][25][26]; thus, concrete with a strength grade of C30 and 20% fly ash were selected in this study. The mixture ratios are shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The aggregate included natural river sand with a fineness modulus of 2.87 and basalt gravel with a continuous gradation of 5-20 mm in particle size. Replacing cement with 20% fly ash had been reported to significantly improve the resistance of concrete to sulfate attack [24][25][26]; thus, concrete with a strength grade of C30 and 20% fly ash were selected in this study. The mixture ratios are shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…MSWI bottom ash was used partially replacing cement. 87 The equivalent substitution of bottom ash for cement reduced the compressive strength of concrete. The maximum ratio of replacing cement with bottom ash was 15% and this binder was suitable for application in low strength concrete.…”
Section: Mswi Residues Recycled As Building Materialsmentioning
confidence: 99%
“…The results showed that after 28 days of curing, the compressive strength of the specimens was almost 40.0 MPa. The authors [26] replaced cement with 10% and 15% of bottom ash in concrete mixes. The studies show that after 28 days of curing, the compressive strength of the cement pastes with W/C ratio of 0.45 reached 29 MPa and 26 MPa, respectively.…”
Section: Compressive Strength Testsmentioning
confidence: 99%
“…Dry-cast concrete with 20% cement replaced by bottom ash showed 18% higher strength [25]. Cheng et al [26] found that the optimal ash content in concrete was between 10% and 15%. Within this range, the ash not only improves the durability of concrete, but also ensures that concrete strength meets the design requirements.…”
Section: Introductionmentioning
confidence: 99%